GORGONEION AND GORGON-MEDUSA: A CRITICAL RESEARCH REVIEW - Anna LAZAROU; Ioannis LIRITZIS (Journal of Ancient History and Archaeology)
Our paper aims at a critical reviewing of the research that has dealt with the Gorgon-Medusa and Gorgoneion (decapitated head) apotropaic feminine beast, as recorded in various artifacts and monuments of the ancient Greek World, from early 19th century until today. Multiple works by ancient sources provide a wide-ranging and diverse picture of the fabled creature and her fateful encounter with the Greek hero Perseus. The use of ancient written historical sources is particularly emphasized and eastern influences on texts and iconography is discussed. As a natural consequence of the interactions, the association of Gorgons with other deities and the Potnia theron (Mistress of Animals) has been variously assessed by scholars with predominant its apotropaic property. Medusa appears in a variety of mythological stories and is depicted in a variety of ways in ancient art. The source of the artistic creation in painting and sculpture is founded on the legends and myths from the remote past, with a sudden appearance and apex in the Greek Archaic period. The review covers the period from prehistory to Late antiquity, whereas, the earliest form of a scarecrow is transformed to the known image of Gorgon/Medusa, and eventually from an ugly to beautiful, a metamorphosis which has been attaching various interpretations. The uniqueness of this “beast” form has emerged through its multifaced representations and mythological reports in the known ancient Greek World of the southeastern Mediterranean and its neighbor areas. Gorgon/Medusa-Gorgoneion in art as witnessed in archaeological remains has been shown to persist in all everyday activities of the ancient World and has been subjected to wide social, cultural, ideological considerations.